Delivering cognitive behavioural interventions in an internet-based healthcare delivery environment. (October 2018) - Nalder, Emily; Marziali, Elsa; Dawson, Deirdre R.; Murphy, Kelly
Introduction: This exploratory qualitative study assessed the feasibility of transitioning three face-to-face, cognitive behavioural interventions for adults with chronic health conditions to online delivery, by examining clinician and clients' satisfaction with intervention training and delivery. Method: The interventions adapted for online delivery were: 'Managing Chronic Disease', a programme for individuals who were nonadherent to prescribed rehabilitation regimens; 'Real-World Strategy Training', an occupation-based intervention for individuals with subjective cognitive decline; and 'Learning the Ropes', a memory programme for persons with mild cognitive impairment. Two occupational therapists and one nurse received training in, and then delivered one of the three interventions. Qualitative feedback interviews with participants, and archived video recordings of intervention sessions were analysed thematically. Results: Key features of each manualised intervention were evident in the online sessions and perceived by clients as enhancing engagement (for example, peer support and strategy training). Clinicians felt that meeting individually with intervention experts was helpful to problem-solve technical issues and ensure adherence to protocols. Conclusion: Three cognitive behavioural interventions transitioned to online delivery were acceptable to older adults and clinicians. A next step would be to complete randomised controlled trials investigating whether the interventions yield equivalent health benefits, using online and face-to-face delivery.